2014
DOI: 10.3402/jev.v3.24015
|View full text |Cite
|
Sign up to set email alerts
|

Antibody‐mediated immunity induced by engineered Escherichia coli OMVs carrying heterologous antigens in their lumen

Abstract: BackgroundOuter membrane vesicles (OMVs) from Gram-negative bacteria are gaining increasing attention as vaccine platform for their built-in adjuvanticity and for their potential use as carriers of heterologous antigens. These 2 properties offer the opportunity to make highly effective, easy to produce multi-valent vaccines. OMVs can be loaded with foreign antigens by targeting protein expression either to the outer membrane or to the periplasm of the OMV-producing strain. Periplasmic expression is simple and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
103
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(122 citation statements)
references
References 42 publications
6
103
0
Order By: Relevance
“…Immunization with OMVs generates strong antigenspecific IgG and/or IgA antibody responses in the serum and in mucosal compartments 22,[76][77][78][79][80][81] . When introduced into the body, OMV antigens are presented by antigenpresenting cells (APCs) to CD4 + T cells 45,70,81,82 , which leads to the generation of antigen-specific B cell responses 45,78,82,83 .…”
Section: Presentation Of Omv Antigens Generation Of Protective Immunementioning
confidence: 99%
See 2 more Smart Citations
“…Immunization with OMVs generates strong antigenspecific IgG and/or IgA antibody responses in the serum and in mucosal compartments 22,[76][77][78][79][80][81] . When introduced into the body, OMV antigens are presented by antigenpresenting cells (APCs) to CD4 + T cells 45,70,81,82 , which leads to the generation of antigen-specific B cell responses 45,78,82,83 .…”
Section: Presentation Of Omv Antigens Generation Of Protective Immunementioning
confidence: 99%
“…When introduced into the body, OMV antigens are presented by antigenpresenting cells (APCs) to CD4 + T cells 45,70,81,82 , which leads to the generation of antigen-specific B cell responses 45,78,82,83 . OMVs can induce protective immune responses during infection with a variety of pathogens -including V. cholerae 81 , H. pylori 80 , S. Typhimurium 45 and Shigella flexneri 84 -and this decreases bacterial burdens [85][86][87] and protects mice from sepsis or death 25,77,79,84,88 (TABLE 1). Adoptive transfer experiments have shown that CD4 + T cells expressing IFNγ and IL-17 were required for OMV-mediated protection in an E. coli-induced sepsis model, which suggests that T helper 1 (T H 1) and T H 17 cell responses may be responsible for protection in this model 88 .…”
Section: Presentation Of Omv Antigens Generation Of Protective Immunementioning
confidence: 99%
See 1 more Smart Citation
“…These characteristics are exemplified by OMVs isolated directly from N. meningitidis, which induce potent protective immune responses and have been incorporated successfully into several commercial vaccine formulations for use in humans (22,24,25). To expand the vaccine potential of OMVs, several groups have used genetic engineering techniques to load OMVs with foreign protein antigens by targeting expression either to the outer membrane or the periplasm of an OMV-producing host strain (26)(27)(28)(29)(30)(31)(32). These OMV-associated recombinant proteins were internalized by eukaryotic cells (26,27) and stimulated strong and specific immune responses in mice (28)(29)(30)(31)(32).…”
Section: Significancementioning
confidence: 99%
“…To expand the vaccine potential of OMVs, several groups have used genetic engineering techniques to load OMVs with foreign protein antigens by targeting expression either to the outer membrane or the periplasm of an OMV-producing host strain (26)(27)(28)(29)(30)(31)(32). These OMV-associated recombinant proteins were internalized by eukaryotic cells (26,27) and stimulated strong and specific immune responses in mice (28)(29)(30)(31)(32). However, although efforts to load OMVs with recombinant protein antigens are well documented (33), an analogous strategy to engineer the polysaccharide component of OMVs for specific vaccine applications has yet to be demonstrated.…”
Section: Significancementioning
confidence: 99%